LEMNA MINOR L. AS A SOURCE OF ANTIOXIDANTS - V. Petrova-Tacheva; V. Ivanov; A. Atanasov (Trakia Journal of Sciences)
Lemna Minor L. (LM) is a perennial aquatic plant that belongs to the genus Lemna, the family Lemnaceae and is spread almost ubiquitously. In folk medicine, it is used in the treatment of allergies, asthma, vitiligo, jaundice, glaucoma, rheumatism, gout, and others. In recent years it has become clear that its chemical composition consists of: proteins (up to 35%), vegetable fibers (up to 17%), fats (up to 5%), polysaccharides, flavonoids, amino acids, aliphatic acids, phenolic acids, triterpene compounds, vitamins, micro- and macro-elements and other substances. А significant part of these substances exhibit the antioxidant activity. The scientific information for 12 biologically active substances with antioxidant activity isolated from Lemna Minor is presented in the review.